The principle of limitation of human rights under the international covenant on economic, social and cultural rights and its reflection in Vietnam’s constitution and law - Bui, Thi Huong (Đại học Quốc gia Hà Nội, 2020)
Human rights have been codified in international law since the Second World War and have become a compulsory international legal standards for all nations. Respecting and protecting of human rights have become a tool of measurement for the level of civilization of all nations in the world. Essentially, human rights are the natural rights of every person, however, a widely accepted view is that the majority of human rights are relative,1 therefore in certain cases these rights might be restricted. The limitation of human rights could be understood as the fact that the State prohibits all entities from exercising their rights at the absolute (highest) level.2 As such, restriction of rights is a common and popular phenomenon in all countries. The limitation of human rights is acknowledged in the Universal Declaration of Human Rights (UDHR) 1948 and a number of international human rights conventions that allow member states to impose certain provisions necessary for the enjoyment of certain rights. Based on the studies of general principles of the limitation of human rights in the International Convenant of Economic, Social and Cultural Rights, this article will make some recommendations for the reduction of limitations for the implementation of a number of economic, social and cultural rights in Vietnam.